2019
DOI: 10.1007/s10067-019-04693-0
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil cytoplasmic antibodies and their relationship with disease activity and presence of staphylococcal superantigens in nasal swabs in patients having granulomatosis with polyangiitis: results of a study involving 115 patients from a single center

Abstract: Objective Antineutrophil cytoplasmic antibodies (ANCAs) are considered a risk factor for granulomatosis with polyangiitis (GPA) exacerbation, especially when staphylococcal superantigens (SAgs) are present in nasal swabs. Their role in monitoring disease activity remains controversial. This study determined the relationship of ANCAs with disease activity and presence of SAgs in GPA patients. Methods Among a total of 115 GPA patients hospitalized in the period 2009-2016, we investigated the presence of SAgs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A subsequent meta-analysis by Tomassen et al was more stringent in its study selection, identifying a modest association at best for persisting ANCA positivity or rising titres with the risk of relapse (17) . Several studies with more longitudinal data, including follow up data from large trials, have since corroborated earlier findings that persistent ANCA positivity, ANCA reappearance and the presence of anti-proteinase 3 (PR3) antibodies are risk factors for relapsing disease (18)(19)(20)(21)(22)(23)(24) . Similarly, seronegativity following remissioninduction therapy is associated with a longer relapse free survival period (18,19) .…”
Section: Ancamentioning
confidence: 57%
“…A subsequent meta-analysis by Tomassen et al was more stringent in its study selection, identifying a modest association at best for persisting ANCA positivity or rising titres with the risk of relapse (17) . Several studies with more longitudinal data, including follow up data from large trials, have since corroborated earlier findings that persistent ANCA positivity, ANCA reappearance and the presence of anti-proteinase 3 (PR3) antibodies are risk factors for relapsing disease (18)(19)(20)(21)(22)(23)(24) . Similarly, seronegativity following remissioninduction therapy is associated with a longer relapse free survival period (18,19) .…”
Section: Ancamentioning
confidence: 57%
“…2 Although correlation between ANCA titers and disease activity has been shown in some studies, the role of ANCAs in monitoring disease activity is contraversial. 6 The onset of the disease is usually at the fourth or fifth decades, thus pregnancy-associated GPA is rare. 3 Singh et al reported that 78 pregnancies with GPA were available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, it still remains unclear which pre-ART factors predispose the immunesystem to trigger this excessive inflammatory response upon ART initiation. Studies on vasculitis have shown that neutrophils express auto-antigens when exposed to antigens [28]. Subsequent binding of so called anti-neutrophil cytoplasmatic antibodies, or ANCAs, leads to the activation of neutrophils and the release of reactive oxygen species, inflammatory cytokines and the corresponding tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Taking a page out of the book of auto-immune diseases, anti-neutrophil cytoplasmic antibodies (ANCAs, a group of antibodies directed against different neutrophilic components), have been widely linked to neutrophil activation and tissue damage in small vessel vasculitides [28,29]. While anti-Myeloperoxidase (MPO) and anti-Proteinase 3 (PR3) are considered the PLOS ONE major components of the ANCA group, antibodies against other components such as bacterial permeability-increasing protein (BPI), elastase, cathepsin, lysozyme, and lactoferrin have all been described in inflammatory conditions which include; inflammatory rheumatic diseases, inflammatory bowel disease, etc.…”
Section: Introductionmentioning
confidence: 99%